The Role of Islamic Boarding Schools in Instilling the Basis of Arabic as the Foundation of Islamic Religious Education in Indonesia - Muhammad Fariq Heemal Attruk (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
Islamic boarding schools (pondok pesantren) play a strategic role in the development of Islamic Education (PAI) in Indonesia, particularly by establishing Arabic language proficiency as a foundation for Islamic literacy. Arabic is not merely treated as a linguistic subject; it is positioned as an epistemological prerequisite for accessing primary sources of Islamic teachings, such as the Qur'an, hadith, and classical texts. This article aims to synthesize narratively the findings of research related to the role of Islamic boarding schools in instilling Arabic proficiency as the basis for Islamic Education in Indonesia. This study employs a Narrative Literature Review (NLR) approach, examining literature sourced from the SCOPUS, GARUDA, and Google Scholar databases. The literature was selected purposively based on its relevance to the context of pesantren, Arabic language learning, and its connection to PAI comprehension. The analysis is conducted through narrative synthesis to identify patterns in findings, learning mechanisms, and the epistemological implications of Arabic within pesantren education. The review reveals that pesantren consistently position Arabic as the epistemological foundation of PAI through the mastery of syntax and morphology (nahwu and sharaf), the habituation of reading classical texts (kitab kuning), the creation of an Arabic-language environment (bi'ah lughawiyyah), and the integration of Arabic into the curriculum and religious activities. Proficiency in foundational Arabic demonstrably has a direct implication on the quality of students' religious understanding, the formation of religious character, and their intellectual readiness for advanced Islamic studies. This article concludes that strengthening Islamic Education in pesantren is inseparable from reinforcing Arabic language proficiency as both a foundational discipline and the primary medium of religious learning. These findings carry significant implications for the development of policy and practice in pesantren education and open avenues for further research concerning the relationship between Arabic proficiency and PAI outcomes across various pesantren models.